Secondary metabolites from higher fungi in Vietnam: Discovery, chemodiversity, and bioactivity - Nguyen, Ngoc Tuan; Tran, Trung Hieu; Nguyen, Thi Ngan; Nguyen, Tan Thanh; Hoang, Van Trung; Nguyen, Thi Bich Ngoc; Kuo, Ping-Chung; Wu, Tian-Shung; Tran, Dinh Thang (Vietnam Journal of Science and Technology, 2022)
Medicinal higher fungi such as Ganoderma lucidum and Phellinus igniarius have been used as alternative medicine remedies to promote health and longevity for people in Vietnam and other regions of the world since ancient times. Nowadays there is an increasing public interest in the secondary metabolites of those higher fungi for discovering new drugs or lead compounds. Current research in drug discovery from medicinal higher fungi involves a multifaceted approach combining mycological, biochemical, pharmacological, metabolic, biosynthetic and molecular techniques. In recent years, many new secondary metabolites from higher fungi have been isolated and are more likely to provide lead compounds for new drug discovery, which may include chemopreventive agents possessing the bioactivity of immunomodulatory, anticancer, etc. However, numerous challenges of secondary metabolites from higher fungi are encountered including bioseparation, identification, biosynthetic metabolism, and screening model issues, etc. Commercial production of secondary metabolites from medicinal mushrooms is still limited mainly due to less information about secondary metabolism and its regulation. Strategies for enhancing secondary metabolite production were continuously developed.